A Review of Two Emerging Rice Diseases, in the Major Rice Growing Areas of the World - Gbadenya, Tokunbo (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
The illness known as kernel smut, which is brought on by Tilletia horrida, is typified by the sooty black masses of teliospores or chlamydospores that replace rice grains. The color of the chlamydospores in kernel smut is different from that of rice fake smut, which is generated by Ustilaginoidea virens. Spore balls that are globose and velvety, with colors ranging from orangish yellow to greenish black, are the hallmark of false smut. Due to their irregular breakouts and little economic impact, kernel smut and fake smut which were first identified in the late 1870s and continued to persist are regarded as minor illnesses in many nations. However, in many nations, particularly the US, kernel smut and fake smut have become two of the most commercially significant illnesses affecting rice, including organic rice, in recent years. Grain production and quality have significantly decreased as a result of the growing use of sensitive rice cultivars particularly hybrids, excessive nitrogen fertilizer use, and short crop rotations. These factors have also led to a rise in kernel smut and fake smut. The distribution and economic significance of kernel smut are reviewed in this article, along with our current knowledge of the taxonomy, biology, and epidemiology of kernel smut and the genomics of the kernel smut fungus in comparison to fake smut and its causative agent. We also provide an update on the current management strategies of pathogen exclusion, cultivar resistance, fungicides, biological control, and cultural practices for kernel smut and false smut of rice.